Adherence to and consumption of nicotine replacement therapy and the relationship with abstinence within a smoking cessation trial in primary care. - Hollands, G; Sutton, S; McDermott, MS; Marteau, T; Aveyard, P (Oxford University Press, 2013)
INTRODUCTION: Nicotine replacement therapy (NRT) medications have been shown to be effective in increasing smoking cessation rates. There is, however, a lack of good evidence describing how individuals in primary care use these medications and which factors are likely to affect this. The study objectives are to describe adherence and consumption, examine key factors that may determine use, and examine the relationship between consumption of NRT and abstinence from smoking. METHODS: Secondary analysis of data from a randomized controlled trial conducted in smoking cessation services in primary care. Adult smokers (n = 633) starting a quit attempt within smoking cessation clinics were followed for 6 months, with NRT use closely monitored for an initial treatment period of 4 weeks. The main outcomes were 4-week adherence to prescribed NRT, mean daily consumption of NRT over the 4-week period, and abstinence from smoking at 4 weeks. RESULTS: Levels of adherence to prescribed NRT were high: more than 94% in participants who completed the treatment period. After controlling for possible confounders, prescribing higher doses of patch and oral NRT was associated with higher mean daily consumption of NRT. Using an inhalator to deliver oral NRT was associated with both higher adherence and higher consumption. The amount of NRT consumed predicted future abstinence when reverse causation was accounted for. CONCLUSIONS: Most individuals within a clinical trial in primary care who persisted with a quit attempt adhered closely to their prescription. Prescribing higher doses of NRT led to higher consumption and higher consumption to higher abstinence.